The Muppet Christmas carol [videorecording (DVD)] - Henson, Brian; Caine, Michael; Goelz, Dave; Whitmire, Steve, 1959-; Dickens, Charles, 1812-1870 (Walt Disney Home Entertainment, 2005)
Miser Ebenezer Scrooge learns the true meaning of Christmas and reforms his heartless and money-grubbing ways after being visited on Christmas Eve by four ghosts. Anniversary edition.